P3.231 Treponema pallidum macrolide resistance surveillance in south africa: 2008–2016. (8th July 2017) - Venter, JME; Müller, EE; Maseko, DV; Kufa-Chakezha, T; S R, Kularatne
Abstract : Introduction: Penicillin is the treatment of choice for syphilis worldwide. Macrolides (e.g. azithromycin [AZM]) have been used as a convenient oral and cost-effective alternative for syphilis treatment in many countries globally. High prevalence macrolide resistance, resulting in treatment failure for primary syphilis in USA, Europe and China has been attributed to an adenine (A) to guanine (G) transition in the 2058 or 2059 position of the Treponema pallidum 23S rRNA gene, resulting in target site alteration due to methylation. In 2014, AZM was added to the syndromic management guidelines for genital discharge in South Africa (SA). Individuals exposed to macrolides are twice as likely to have a resistant strain of T. pallidum within the next year. We sought to ascertain the prevalence of macrolide resistance-associated T. pallidum in genital ulcer disease (GUD) specimens from patients, presenting to nine primary health care facilities (PHCs) (one PHC per province) in SA, between 2008 and 2016. Methods: Swab samples from genital ulcers were collected from 2238 adult patients (>18 years of age) presenting to PHCs throughout SA. Macrolide resistance testing was done using established polymerase chain reaction (PCR) and restriction digest assays described by Lukehart et al ., (2004) and Matejkova et al ., (2009) on the G-Storm platforms (Vacutec). The resultant 628 base-pair (bp) fragment of the 23S rRNA gene was submitted to digestion with BsaI - and MboII -restriction enzymes to screen for the A2059G and A2058G mutations respectively. Amplicons with A2058G and A2059G mutations resulted in 2 distinct band sizes for each mutation. The SS14 strain (A2058G mutation), the A2059G (+) strain, and the wild-type Nichols strain were included as controls. Results: T. pallidum was detected in 105/2, 238 (4.7%) GUD specimens collected over a nine-year surveillance period. The A2058G mutation was detected in 4/105 (3.8%) specimens. The A2059G mutation was not identified. All specimens having macrolide resistance-associated mutations in T. pallidum were obtained in the years 2013 to 2016. Conclusion: This is the first report of macrolide resistance-associated mutations detected among T. pallidum in SA. Ongoing surveillance for AZM resistance is essential to inform future management guidelines.